The Impact of ESG Disclosure on Firm Value: Systematic Literature Review Approach - Lulu Islami Nur Afifah; Sekar Ayu Cahyaningtyas; Wisnu Mawardi (Arthatama: Journal of Business Management and Accounting, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosure on firm value using a Systematic Literature Review (SLR) approach. The growing global emphasis on sustainable business practices has made ESG disclosure a key instrument in signaling corporate responsibility and long-term value creation. However, empirical findings across sectors and regions remain inconsistent. This paper synthesizes 30 reputable international articles (indexed as Q1/Q2) from 2020 to 2025 to identify prevailing patterns and gaps. The results show that many studies report a significant positive relationship between ESG disclosure and firm value. Nevertheless, only a minority of studies explore profitability as a moderating variable, and its moderating effect appears statistically insignificant. The review highlights that organizational characteristics such as firm size may play a more decisive role in enhancing the value effects of ESG disclosure. The paper contributes to sustainability literature by offering an integrated conceptual framework and suggesting future empirical directions, particularly concerning moderating variables in different institutional and industrial contexts.